CAPITAL MARKET REACTIONS TO THE ANNOUNCEMENT OF PPKM IMPLEMENTATION (EMPIRICAL STUDY at COMPANY in LQ45 INDEX) - Andhika Yanuardan Utomo; Siti Atikah; Robith Hudaya (Journal of Finance, Economics and Business, 2023)
This study aims to measure how the Indonesian capital market reacts to the announcement of the implementation of the 11 July 2021 Community Activity Restrictions. This research uses an event study as an approach. The population in this study was LQ45 for the period June - July 2020. The sampling technique used purposive sampling with 45 companies as the selected sample. This study uses the variable average abnormal return as a variable and trading volume activity. Wilcoxon signed rank is used as a test tool with the results of this study showing that there is no significant difference in the average abnormal return before and after the announcement of PPKM because it has test results with a value of 0.148> 0.05. In addition, this study shows that there is no significant difference in trading volume activity before and after the announcement of the PPKM. This is shown from the results of the Wilcoxon signed rank significance test which has a value of 0.743 > 0.05. The implications of research can provide information and benefits to decision makers regarding the impact of the information content of an event on stock prices. For investors it can be used as a signal in their taking action on the capital market